Book Review: Roth, M. S. (2014). Beyond the university: Why liberal education matters. Yale University Press - Enemuwe, Christopher Amrobo (Bahir Dar Journal of Education, 2025)
This review assesses the book titled “Beyond the university: why liberal education matters” authored by Michael Scott Roth. It underscores essential aspects pertinent to contemplation on the evolution of America’s liberal arts education, specifically and education in general, which bear significant implications and insights for its current condition. The book offers a comprehensive and detailed explanation of the evolution of liberal arts education in the United States of America and argues that shifting away from the broad humanistic educational approach aimed at long-life learning to vocational training in liberal arts education is a critical mistake. The insights gleaned from such lessons hold significant importance for regions such as Africa and the black community, particularly considering the recent advocacy for a more vocational approach to liberal arts education driven by the demands of skill-based labour.